RONGO-RONGO DALAM PEMENUHAN KEBUTUHAN RUMAH TANGGA - Riki Bugis; Sofian Malik; Rudy Kurniawan; M. Chairul Basrun Umanailo; Hayati Hehamahua (Centre for Asian Social Science Research (CASSR), FISIP, UIN Bandung, 2019)
The term rongo-rongo is a burden-bearing worker in the namlea market. As a carrier, the rongo-rongo load up each item that is thought by the customer and follows the conscription for shopping. Occupational risks and health hazard do not prevent them from continuing to keep busy to meet the economic family. This study is a qualitative study that describes the existence of the rongo-rongo in order to meet the needs of the home. The location of this study is in the village Karang jaya, market namlea, namlea terminal, with visibility for informant activity. Studies have shown that the existence of rongo-rongo is a major pilar of the household’s living resources, an effort to control household needs is done by focusing on physical strength without considering ill-health risks. In addition to making up for needed, the rongo-rongo does the activities outside of the main work o.g cleaning up stores of laundry and agricultural product.